(untitled) (Indian Journal of Pure & Applied Physics (IJPAP), 2024)
The materialistic particles have remarkable technological application at size of nano scale (1-100 nm). The metal such as zinc and manganese have enhanced properties in field of Optical, Magnetic, Electrical and Biogenic field because of valence d-orbital electrons with great efficiency. In present work,the researcher synthesized pure ZnO and 10% Mn doped ZnO nano particulates via microwave irradiated chemical co-precipitation protocols andthen as synthesized samples were calcined at 200, 400 & 600 oC for 2hrs. The powdered sample of pure and ZnO and Mn doped ZnO were examined through XRD, FTIR, FESEM and HRTEM characterization tools. The XRD results indicates that wurtzite crystalline were in formation with crystallite size increase with increase of calcinations temperature. The intensity of absorption was increases with increase of calcinations temperature 200, 400 & 600 oC for 2hrs.The IR absorption peak at about 403, 404, 413cm-1 & 638, 658, 669 cm-1 were assigned to O-Zn-O and O-Mn-O vibration of ZnO & MnO2 respectively. The morphological studies of particles were examined by electron microscopic tools FESEM and HRTEM. The magnified images of MnO/ZnO sample indicates that single phase hexagonal structure was formed and morphology of ZnO pure particles were spherical whereas, MnO/ZnO calcined at 600 oC 2hrs were 2D nanosheet occurrence in nature. The photoluminescence (PL) study of various samples concluded that newer material has primary excitation energy level at about 303, 305, 307nm and secondary exciton energy level 471, 474, 477nm whereas, the emissive transition occurred at position 661, 665, 668nm for 10% Mn doped ZnO crystalline calcined at 200, 400 & 600 oC for 2 hrs respectively. The newer calcined materials have remarkable properties in field of optoelectronics as the material have optical band gap at about 1.8 eVto 1.90 eV respectively and may have provoked application in field of herbicide and bactericidal applications in presence of sunlight.